The relation between physical and mental illness : the physical status of psychiatric patients at a multiphasic screening survey - Eastwood, Michael Robin, 1938- (Monograph series (Clarke Institute of Psychiatry), 1975)
This volume presents the findings of a study carried out, at a community health screening survey, to test the association between physical and psychiatric disorder. It is suggested that the findings, which confirm the two types of morbidity, have implications for the delivery of health care and preventive medicine.